Microneedles: promising technique for transdermal drug delivery. - JAYDEEP D YADAV; KUMAR A VAIDYA; PRIYANKA R KULKARNI; RAJVAIBHAV A RAUT. (International Journal of Pharma and Bio Sciences, 2011)
Transdermal drug delivery using microneedle is a novel method of drug delivery. Microneedle is like conventional needles only fabricated in micro scale. The advantage of using microneedle is that it does not pass the stratum corneum. The dosing in microgram quantities can be done by this type of needle. The mechanism of action is based on temporary mechanical disruption of skin. The drug, in the form of biomolecules, is encapsulated within the microneedles, which are then inserted into the skin in the same way a drug like nitroglycerine is released into the bloodstream from a patch. The needles dissolve within minutes, releasing the trapped cargo at the intended delivery site. The review covers the various methods of drug delivery like Poke with patch approach, Coat and poke approach, Biodegradable microneedles, Hollow microneedles and Dip and scrape. The various method of preparation of microneedles include molding, casting, laser cutting. The in vivo safety assessment and the evaluation of microneedle have shown that this technique can be used safely. There are various advantages of the microneedle trans dermal drug delivery methods over other techniques which helps to make it successful delivery system.